Reinterpretasi Teologis Steriotipe Perempuan sebagai Paboru dalam Struktur Tolu Sahundulan Lima Saodaran - Saragih, Erman Sepniagus (Indonesian Journal of Theology, 2024)
This article questions the stereotypes of women in the Tolu Sahundulan Lima Saodoran (TSLS) kinship system in Simalungun, which is conspired by constructing patriarchal theology and intertwining it to form a collective consciousness. The reinterpretation was carried out to stimulate awareness that women are not only placed in a definitive meaning function based on traditional demands, but it is time for them to be aware of progress in the form of a presence in a new meaning in public spaces. The method used is descriptive qualitative research, interview approach, and secondary literature study with the principles of dialogue and criticism of feminist theology. The conclusion is that it is essential to read and reinterpret the image of women’s inferiority and stereotypes of women in the Simalungun traditional structure pioneered by GKPS, Simalungun women scholars, and women theologians. The meaning of labor in TSLS is similar to how God expressed His motherly love to the Israelites in the desert and the 5,000 hungry people and how Jesus gave life through table service by providing bread and wine. Thus, the customary legal obligations for women’s clans are significant to interpret theologically because successful implementation of customs will not be achieved without paboru as a manifestation of the existence of a mothering God who cares for His people and gives life.